Pollen Content in Honey of Apis mellifera Linnaeus (Hymenoptera, Apidae) in an Atlântica Forest Fragment in the Municipality of Piracicaba, São Paulo State, Brazil - Araujo, Diogo Feliciano Dias; Moreti, Augusta Carolina Carmelo Carmargo; Silveira, Talita Antonia da; Marchini, Luís Carlos; Otsuk, Ivani Pozar (Sociobiology (Chico, CA), 2013)
The productive and reproductive characteristics of Apis mellifera L. bees are directly affected by climatic conditions and food availability in the region where the bees are reared or kept; therefore, food storage (honey and pollen), oviposition and population growth of these bees are subject to seasonal variations. These variations lead the bees to constantly search for food, taking exploratory trips, called “foraging”. This study investigated the botanical origin of nectar sources collected by A. mellifera bees for six consecutive months, from October/2011 to March/2012 in six bee colonies. The study was carried out in the experimental apiary of the Entomology and Acarology Department of the College of Agriculture “Luiz de Queiroz”, from the University of São Paulo, in the municipality of Piracicaba, São Paulo State. The study site has a predominance vegetation of Semideciduous Forest (Atlântica Forest). In each sampling month, we analyzed the pollen types in the honey samples. We used the acetolysis method to prepare the samples for melissopalynology. We carried out the quantitative analysis by successive count of 900 sample grains. The samples were grouped in terms of botanical species, families and/or pollen types. The results show that bees used several plants from the region as a nectar source. However, Arecaceae, Fabaceae/Mimosoideae and Myrtaceae families were predominant throughout the sampling period. The occurrence of these plant species was significant and essential for the maintenance of the bee colonies.